The Role of Logistics Infrastructure in China Pakistan Economic Corridor Energy Generation Development - Idrees, Rao Qasim; Shapiee, Rohimi; Ahamat, Haniff (International Journal of Energy Economics and Policy, 2018)
Providing cheap and adequate supply of electricity is the backbone of the economy of country. It is recognised worldwide that key sectors of the country including trade, business, manufacturing, agriculture are heavily dependent on uninterrupted electricity supply. In addition, fast progress of the country and well being of the people is linked with strong and proper logistics management system. Pakistan has been encountering terrible energy shortage for almost last two decades. Considering such energy deficiency, this article provides broad information of the energy and logistics management in Pakistan and the problems it is dealing with. Furthermore this article provides the comprehensive frame work of China Pakistan Economic Corridor (CPEC) energy projects and analyse how logistics sector improvement can overcome energy deficit. In addition, this article examines the various factors which are responsible for the uneven power supply in the country. This article concludes that without upgrading logistics infrastructure the energy deficit would not be handled. Therefore, in such situation, as per CPEC logistics and infrastructure investment strategy, Pakistan can get consistent, excessive and cost effective power supply in order to streamline ever increasing energy needs and also ensures sustainable economic development of the country. Keywords: China Pakistan Economic Corridor, energy generation, logistics infrastructure, renewable energy JEL Classifications: Q40, Q41, Q47, Q48 DOI: https://doi.org/10.32479/ijeep.7045